2014
DOI: 10.1186/1472-6882-14-146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gelam and Acacia honey acute administration on some biochemical parameters of Sprague Dawley rats

Abstract: BackgroundSince ancient times, honey has been used for medicinal purposes in many cultures; it is one of the oldest and most enduring substances used in wound management. Scientific evidence for its efficacy is widely studied, but systemic safety studies are still lacking. It is essential to study the impact of consumption of honey on the health and proper development of the consumer. Therefore, the present study was designed to observe the effects of acute administration (14 days) of Gelam honey (GH), a wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
(22 reference statements)
2
21
0
Order By: Relevance
“…Intubation of 2 g/kg/day BGH significantly reduced the liver damage, which was almost similar to the effect of glibenclamide. Similar results were observed in rats treated with Tualang, Gleam, and Apica honey [50][51][52]. The increased urea and creatinine levels in the serum indicates impaired renal function [53].…”
Section: Discussionsupporting
confidence: 79%
“…Intubation of 2 g/kg/day BGH significantly reduced the liver damage, which was almost similar to the effect of glibenclamide. Similar results were observed in rats treated with Tualang, Gleam, and Apica honey [50][51][52]. The increased urea and creatinine levels in the serum indicates impaired renal function [53].…”
Section: Discussionsupporting
confidence: 79%
“…According to Table 3, almost no significant difference was detected in all biochemical parameters after administration of CMSN (except GLB and TP). 18,[42][43][44] The results indicated that CMSN did not promote severe abnormalities of the hepatic and renal functions, and was proven to be safe in vivo. Based on the in vitro and in vivo results, it was reasonable to speculate that CMSN was a biocompatible bio-material with negligible toxicity, and was suitable for further applications in biological fields.…”
Section: In Vivo Toxicitymentioning
confidence: 91%
“…In an animal model, Samat et al [ 73 ] observed the effects of GH acute administration on biochemical parameters. Rats fed with 2000 mg/kg body weight of GH did not show any adverse effects or deaths.…”
Section: Other Health Benefits Of Ghmentioning
confidence: 99%